Agenda Setting Pemerintah DKI Jakarta dalam Kebijakan Pengelolaan Sampah TPST Bantar Gerbang - Gabriel, Reynaldo; Bandiyah, Bandiyah; Noak, Piers Andreas (Jurnal Nawala Politika, 2020)
ABSTRACT Waste management in DKI Jakarta always heading toward difficult way, and even nowadays it become a political commodity that politicians able to use for the purpose of Election. The purpose of this research is to know the policies flow in policy making concepts in the development of the Intermediate Treatment of the Governor of DKI Jakarta and the DKI Jakarta DPRD. John Kindong's Theory. This study uses descriptive qualitative. The results of this study indicate: First, the condition of Bantargebang TPST which will be overload in the moment of 2019 Election, secondly many NGOs were disagree in the construction of ITF Jakarta based on the uses of incinerator combustion system, third The National Government uses BPPT to perpetuate interests in ITF development using incinerators, the Fourth Revision of Law No. 3 of 2013 concerning waste management is a subjective. Keyword: Agenda Setting, Actor and Waste management politics